Gingival Wound Healing: An Essential Response Disturbed by Aging?. (March 2015) - Smith, P.C.; Cáceres, M.; Martínez, C.; Oyarzún, A.; Martínez, J.
Gingival wound healing comprises a series of sequential responses that allow the closure of breaches in the masticatory mucosa. This process is of critical importance to prevent the invasion of microbes or other agents into tissues, avoiding the establishment of a chronic infection. Wound healing may also play an important role during cell and tissue reaction to long-term injury, as it may occur during inflammatory responses and cancer. Recent experimental data have shown that gingival wound healing is severely affected by the aging process. These defects may alter distinct phases of the wound-healing process, including epithelial migration, granulation tissue formation, and tissue remodeling. The cellular and molecular defects that may explain these deficiencies include several biological responses such as an increased inflammatory response, altered integrin signaling, reduced growth factor activity, decreased cell proliferation, diminished angiogenesis, reduced collagen synthesis, augmented collagen remodeling, and deterioration of the proliferative and differentiation potential of stem cells. In this review, we explore the cellular and molecular basis of these defects and their possible clinical implications.